Characterizing remarkable changes of severe haze events and chemical compositions in multi-size airborne particles (PM1, PM2.5 and PM10) from January 2013 to 2016–2017 winter in Beijing, China. (September 2018) - Shao, Panyang; Tian, Hezhong; Sun, Yujiao; Liu, Huanjia; Wu, Bobo; Liu, Shuhan; Liu, Xiangyang; Wu, Yiming; Liang, Weizhao; Wang, Yong; Gao, Jiajia; Xue, Yifeng; et al.
Abstract: Severe hazes occurred during 2016–2017 winter manifested winter haze was still a tough challenge in Beijing since the unprecedented haze in January 2013. Three haze episodes were identified from December 15, 2016 to January 15, 2017 in Beijing: the Red-Alert episode, the mixed haze-dust episode and the longest and heaviest Cross 2017 New Year's Haze episode. We analyzed the chemical components (water-soluble inorganic ions, carbonaceous components and trace elements) of multi-size airborne particles (PM1, PM2.5, PM10 ) samples, as well as the associated gaseous pollutants and meteorological parameters. Compared with the well-documented severe haze in January 2013, 2016–2017 winter haze was characterized by more stagnant synoptic conditions, sustained accumulation growth of PM enhanced by secondary reactions and regional contribution, as well as prominent fine particles mainly constituted by high concentrations of carbonaceous aerosol, secondary inorganic ions and anthropogenic elements. With strict pollution control measures since the enacting of Clean Air Action Plan in 2013, ambient concentrations of SO2, as well as SO4 2− and most anthropogenic elements in PM2.5 have decreased, whereas N O 3 − and N H 4 + concentration in PM2.5 increased by as high as 77.9% and 47.3% respectively compared with January 2013. The ratios of N O 3 − / S O 4 2 − in PM1, PM2.5, PM10 were higher than 1.0 no matter during normal period or haze period, totally different with the results in January 2013, which suggested the increased relative contribution from mobile sources and decreased contribution from coal combustion in Beijing. Nitrate and its precursors had become major concerns during winter haze in Beijing, although the rapid growth of sulfate still played an important role in the formation and evolution of extremely heavy haze events. Under ammonium-rich and high relative humidity conditions, N O 3 − was thought to mainly be produced by enhanced heterogeneous reactions. To prevent Beijing winter haze effectively, it's quite crucial to cut NOx, NH3, SO2 and VOCs emissions simultaneously and strengthen regional cooperation on air pollution control. Graphical abstract: Image 1 Highlights: Characteristics, precursors and sources of PM2.5 have changed obviously since the enacting of Clean Air Action Plan in 2013. Compared with January 2013, SO2, SO4 2− and trace elements in PM2.5 decreased, whereas NO3 − and NH4 + increased significantly. 2016–2017 winter haze is featured with more stagnant meteorology and sustained accumulation of PM2.5 enhanced by regional transport and secondary reactions. Carbonaceous aerosol (OC, EC) and secondary inorganic aerosol (SO4 2−, NO3 − and NH4 + ) were two major parts in PM with fine-mode size distributions.